PERLINDUNGAN HUKUM BAGI ISTRI DALAM KOMPILASI HUKUM ISLAM DI INDONESIA - Fitrah Erlan Sosadi P. Siregar; Tarmizi Herianto; Doni Syaputra Nasution; Samsul Hidayat Daulay; Ahmad Aspar Siregar; Muhammad Fazri; Amru Hasibuan (LPPM IAI Dar Aswaja Rokan Hilir, 2026)
This study aims to analyze the implementation of legal protection for wives under the Compilation of Islamic Law (KHI) in Indonesia, highlighting the gap between normative legal texts and judicial reality. The core problem of this research lies in the persistently low level of fulfillment of wives' economic rights post-divorce, such as iddah maintenance and mut'ah, which are often neglected due to weak execution mechanisms, constraints of verstek judgments, and patriarchal cultural dominance. The research method employed is normative juridical with a statutory approach and a conceptual approach. Data were collected through a literature study of primary, secondary, and tertiary legal materials, then analyzed descriptively-qualitatively using content analysis. The findings reveal that although KHI normatively guarantees fundamental rights for wives, its practical implementation remains weak, with judicial data indicating that only approximately 2.73% to 3% of divorce decisions effectively include the fulfillment of these economic rights. However, positive developments have emerged through the Supreme Court's progressive judicial ijtihad, such as PERMA No. 3 of 2017 and SEMA No. 3 of 2018, which address legal voids in the KHI by mandating alimony payment prior to the pronouncement of the divorce pledge. The conclusion of this study emphasizes that the success of legal protection for wives in Indonesia depends heavily on the synchronization between gender-responsive regulations and the reinforcement of a more effective and compelling enforcement oversight system.